Syntactic ambiguity of (complex) nominal groups in technical English - Borucinsky, Mirjana; Kegalj, Jana (International Journal of English Studies, 2019)
Complex nominal groups are common in technical English (i.e. English for Specific Purposes, ESP) as they allow lexical items to be tightly packed into a clause. This leads to increased lexical density and syntactic ambiguity. In this paper we analyze (complex) nominal groups in technical English, assuming that it is not only the context and extralinguistic knowledge (i.e. shared technical background that the ESP teacher does not necessarily possess) that help solve the syntactic ambiguity, but that the structure of the nominal group, or more precisely the position of modifiers within the group can help disambiguate the meaning. Thus, modifiers standing farthest from the head have the least specifying potential and are followed by those which restrict the meaning of the entire nominal group. In the example steam reciprocating engine (vs.*reciprocating steam engine) the participle reciprocating has a more specific meaning and is thus closer to the head of the nominal group. The results show how the type of modification (linear or non-linear) can help disambiguate complex nominal groups. The main contribution of the paper is to help the ESP teacher, who is not a specialist in the field of (marine) engineering, process, understand and successfully teach complex nominal groups.